The Impact of push-pull factors on the re-expatriation intention among Jordanian self-initiated academic repatriates - Abdel-Rahman, Gheath M. A. (2019)
To date, majority of the studies on global mobility among professionals have been concentrating on expatriation and repatriation. However, little is known about the phenomenon of second re-expatriation after one has completed the repatriation process. The uncontrolled re-expatriation can be detrimental to developing countries like Jordan which relies on its critical human capital to develop the nation. Using the Push-Pull Theory and Social Capital Theory, this study examined the combined effects of push-pull factors on re-expatriation intention among Jordanian academic repatriates. Partial Least Squares – Structural Equation Modeling (PLS-SEM) was used to confirm the reliability and validity of the measurement model and to test the hypothesized relationships. Using a sample of 124 Jordanian academic repatriates obtained through snowball sampling, this study found that selected home country push factors, namely financial difficulties and re-entry hardships, were positively associated with their re-expatriation intention. Results of the study revealed that host country pull factor, namely family outcomes, had a positive impact on their re-expatriation intention. Additionally, this study also found that life dissatisfaction mediates the relationship between home country push factors and the intention to re-expatriate. Psychological well-being found mediates the relationship between host country pull factors and the intention to re-expatriate. The mediation support indicates that psychologically related factors such as life dissatisfaction and psychological wellbeing serve as the important underlying mechanism responsible to explain individual behavior in intercultural setting. This study fills the gap in the expatriation literature by examining the impact of financial, psychological, and social factors that drive expatriates to move abroad for the second time after their repatriation to their home countries. The results of this study will help relevant decision makers and government agencies to devise appropriate strategies and policies to retain expatriates in their home countries.